A Comparative Study of the Removal of Smear Layer by Two Endodontic Irrigants and Nd:YAG Laser: A Scanning Electron Microscopic Study. (14th July 2012) - Hasheminia, Seyed Mohsen; Birang, Reza; Feizianfard, Mahboobe; Nasouri, Mina
Abstract : The aim of this study was to compare the effect of 17% EDTA, 5% maleic acid, and Nd:YAG laser on smear layer removal by SEM. Eighty single-rooted teeth were divided into three groups of 25 according to the final procedure for smear layer removal: irrigation by 17% EDTA or 5% maleic acid or Nd:YAG laser irradiation. The other five teeth was used as control. Roots were sectioned into buccal and lingual parts, and smear layer presence was recorded in the coronal, middle, and apical thirds under SEM. Data were analyzed by Kruskal-Wallis, Mann-Whitney, Friedman, and Wilcoxon tests. There was no significant difference between smear layer removal of 17% EDTA and 5% maleic acid. Nd:YAG laser showed the least effect significantly. The coronal part of samples was significantly cleaner than the middle, and the middle was cleaner than the apical section. 17% EDTA and 5% maleic acid were more effective in smear layer removal compared to Nd:YAG laser.